Base flow characteristics for a sub-scale high-speed exhaust at over-expanded mode - Tsentis, Spyros; Goulos, Ioannis; Prince, Simon A.; Pachidis, Vassilios; Zmijanovic, Vladeta (International Council of the Aeronautical Sciences (ICAS), 2024)
This paper presents a numerical investigation on the base flow characteristics of a sub-scale, high-speed exhaust system at over-expanded state. The geometry is representative of future, advanced propulsion concepts. It features a truncated, ideal-contoured (TIC) nozzle and an axisymmetric cavity embedded at the base. Scale resolving simulations are performed using the Delayed Detached Eddy Simulation (DDES) turbulence modelling approach. The configuration is mounted on the test section of a wind tunnel through a wing-pylon to facilitate ongoing experiments. The proper orthogonal decomposition (POD) method is employed to identify the salient flow features at the base in terms of energy content. Time-averaged base pressure results show slightly reduced levels of pressure behind the pylon by approximately 1.2%. Additionally, reduced levels of pressure fluctuations in the region directly downstream of the pylon are identified, suggesting a severe impact on the base flow. This is further confirmed through the modal decomposition of the base flow. The first two most energetic modes of the flow exhibit strong spatial asymmetry in the intensity of velocity fluctuations, the latter being significantly reduced in the region behind the pylon. This is important for future, high-speed vehicles, which typically employ wingtip mounted nacelles and could exhibit increased levels of side loads as a result of this azimuthal asymmetry in the flow development.
Keywords: base flow; high-speed exhausts; base drag; DDES; POD